Fatigue crack initiation behaviors throughout friction stir welded joints in AA7075-T6 in ultrasonic fatigue. (December 2015) - He, Chao; Liu, Yongjie; Dong, Jiangfeng; Wang, Qingyuan; Wagner, Daniele; Bathias, Claude
Highlights: Gigacycle fatigue strength of FSW joint in AA7075 was obtained. Two kinds of particles control the fatigue crack initiation. Micro cracks shorten the fatigue life of thermo-mechanically affected zone greatly. Distribution of particles was influenced by recrystallization process. Abstract: This paper presents the results of experimental investigation on fatigue behaviors of friction stir welded joints in AA7075-T6 with ultrasonic fatigue test system (20 kHz). Two kinds of particles, Fe-rich intermetallic compounds and Mg2 Si-based particles, governed the fatigue crack initiation. The plastic deformation and recrystallization during welding process led to the changes in particle size and micro crack occurrence between thermo-mechanically affected zone (TMAZ) and nugget zone (NZ). Therefore, the fatigue crack initiation sites leaned to be located at the TMAZ in short fatigue life, or at the NZ in very high cycle fatigue regime.